Traditional Marriage Practices of the Javanese Community in Langkat District, North Sumatra: An Islamic Legal Perspective - Ishaq Ishaq; Asmuni Asmuni; Sudirman Suparmin (Universitas Islam Sultan Agung, 2023)
Marriage in Islamic law has been clearly stated regarding its pillars, conditions, and the permissible and prohibited provisions. This study aims to analyze the Javanese customary marriage practices of the people in Langkat Regency, North Sumatra Province, considering that the community still strongly adheres to various wedding processes as inherited from their ancestors, from the perspective of Islamic law. This research is empirical and uses a social approach. The data analysis employed is the Miles and Huberman model, with the steps of data reduction, data display, and conclusion drawing and verification. In practice, Javanese customary marriages among the people of Langkat Regency still feature a series of traditional Javanese wedding ceremonies, even though they live outside Java Island. The analysis of Islamic law's perspective on Javanese customary marriage shows a dynamic interaction between cultural traditions and religious principles. Determining auspicious wedding days based on 'primbon' can be accepted in Islam as long as it does not involve beliefs in supernatural elements contrary to Islamic law. Furthermore, the practices of 'kembar mayang' and 'pecah telur' in Javanese customary marriage are considered 'urf fasidah (customs contrary to Islamic law) because they involve beliefs in things not based on Islamic teachings. The accommodation process of Islamic law in Javanese marriage customs demonstrates a harmonious integration effort between religion and culture. From an Islamic viewpoint, cultural traditions can be accepted and integrated as long as they do not conflict with the fundamental principles of the religion.